Implementasi Media E-commerce pada Pemasaran Kain Sutra Mandar di Polewali Mandar - asmawati s; Dian Megah Sari (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
The purpose of this research is to develop an information system that is used to improve the marketing of mandar silk sarong products, as well as to determine the practicality and effectiveness of the software in implementing e-commerce-based marketing of mandar silk sarongs. This research is a type of R & D (Research and Development) research using a prototype development model. The results of system design include two parts, namely: a page that can be accessed by visitors and customers and an admin page that is used to manage detailed information in storing information related to the product being marketed. Marketing that uses e-commerce media can provide convenience in the process of checking goods, ordering processes, and payments to stores and consumers or so as to build better reciprocal relationships